High Refractive Index Metamaterial Superstrate for Microstrip Patch Antenna Performance Improvement - Gao, Xi; Zhang, Yan; Li, Simin (Frontiers in Physics, 2020)
We propose a high refractive index metamaterial (HRIM)that is composed of two identical patch arrays symmetrically etched on both sides of a dielectric plate. By reducing the gap of adjacent patches and the thickness of dielectric plate, the proposed metamaterial can suppress the diamagnetic response and enhance the capacitance coupling, so that the refractive index of the metamaterial is higher than 10 in wideband from 4 to 8 GHz. Attributing to the property of high refractive index, the metamaterial can effectively improve the performance of a microstrip antenna when it is loaded as a superstrate. The measured results reveal that the antenna has an impedance bandwidth (S11 < −10 dB) of 690 MHz (12.4%) and a maximum gain of 13 dB appearing at 5.6 GHz. The 1 dB and 3 dB gain bandwidths are 380 MHz (6.7%) and 590 MHz (10.3%), respectively. Fortunately, the profile of the antenna is only 0.19λ0 (λ0is the free space wavelength at central frequency). Furthermore, the profile can be further reduced to 0.15λ0 when the radiation patch of the antenna is surrounded by another metamaterial.